Occupational stress management strategies in a competitive work environment: impact on performance and turnover intention - Pelealu, Deasy Rinayanti (International Journal of Enterprise Modelling, 2025)
A competitive work environment often creates stress that negatively impacts employee performance and increases turnover intention. This study aims to explore the relationship between job stress, performance, and turnover intention, and analyze the effectiveness of stress management strategies in reducing these negative impacts. Using a survey-based quantitative approach, data was collected from 100 employees in the technology, banking, and consulting sectors who faced high performance pressure. The research instruments included the Perceived Stress Scale (PSS), Job Performance Scale, and Turnover Intention Scale. Data analysis showed that job stress had a significant negative correlation with performance (r = -0.53, p < 0.01) and a significant positive correlation with turnover intention (r = 0.62, p < 0.01). Stress management strategies, such as stress management training and work-life balance programs, were found to be effective in improving employee performance and reducing turnover intention. This study provides practical implications for organizations to design stress management strategies based on sector needs, in order to create a healthier, more productive and sustainable work environment. Further studies are recommended to explore more innovative stress management interventions and their impact on other organizational aspects, such as job satisfaction and organizational culture.